Chromosome 1 Sequence Analysis of C57BL/6J-Chr1KM Mouse Strain - Fuyi Xu; Tianzhu Chao; Yiyin Zhang; Shixian Hu; Yuxun Zhou; Hongyan Xu; Junhua Xiao; Kai Li (International Journal of Genomics)
The Chinese Kunming (KM) mouse is a widely used outbred mouse stock in China. However, its genetic structure remains unclear. In this study, we sequenced the genome of the C57BL/6J-Chr1KM (B6-Chr1KM) strain, the chromosome 1 (Chr 1) of which was derived from one KM mouse. With 36.6× average coverage of the entire genome, 0.48 million single nucleotide polymorphisms (SNPs) and 96,679 indels were detected on Chr 1 through comparison with reference strain C57BL/6J. Moreover, 46,590 of them were classified as novel mutations. Further functional annotation identified 155 genes harboring potentially functional variants, among which 27 genes have been associated with human diseases. We then performed sequence similarity and Bayesian concordance analysis using the SNPs identified on Chr 1 and their counterparts in three subspecies, Mus musculus domesticus, M. m. musculus, and M. m. castaneus. Both analyses suggested that the Chr 1 sequence of B6-Chr1KM was predominantly derived from M. m. domesticus while 9.7% of the sequence was found to be from M. m. musculus. In conclusion, our analysis provided a detailed description of the genetic variations on Chr 1 of B6-Chr1KM and a new perspective on the subspecies origin of KM mouse which can be used to guide further genetic studies with this mouse strain.